2021
DOI: 10.1186/s43055-021-00512-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low-dose chest CT protocol during the second wave of COVID-19 pandemic: a double-observer prospective study on 250 patients to evaluate its detection accuracy

Abstract: Background While the second wave of COVID-19 pandemic almost reached its climax, unfortunately, new viral strains are rapidly spreading, and numbers of infected young adults are rising. Consequently, chest high-resolution computed tomography (HRCT) demands are increasing, regarding patients’ screening, initial evaluation and follow up. This study aims to evaluate the detection accuracy of ultra-low-dose chest CT in comparison with the routine low-dose chest CT to reduce the irradiation exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Regarding the pitch number, some studies suggest a pitch of less than 1 to have an image with enough quality to detect the ground-glass nodules ( Niu et al, 2021 ). However, other studies used pitch numbers of 1.4 and 1.5 and slice thickness of 5 mm, satisfying the results ( Samir et al, 2021a ; Song et al, 2020 ), similar to the results of H4 in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the pitch number, some studies suggest a pitch of less than 1 to have an image with enough quality to detect the ground-glass nodules ( Niu et al, 2021 ). However, other studies used pitch numbers of 1.4 and 1.5 and slice thickness of 5 mm, satisfying the results ( Samir et al, 2021a ; Song et al, 2020 ), similar to the results of H4 in this study.…”
Section: Discussionsupporting
confidence: 89%
“…They reported that they could reduce the mean effective dose from 0.85 (low-dose protocol) to 0.59 mSv/mGy cm (ultra-low-dose protocol) by reducing mAs from 45 to 22. They also stated that ultra-low-dose CT did not affect the diagnostic efficiency ( Samir et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…A similar conclusion was reached by Samir et al in a prospective study comparing ultra-low-dose CT with a 22 mAs tube current and low-dose CT. The former had excellent inter-observer agreement (96-100%) and 90.38-93.84% accuracy in COVID-19 imaging [18]. Tabatabaei et al obtained similar results on a small sample of 20 patients with an intraclass correlation of 0.98-0.99 for detecting COVID-19 pneumonia using a 30 mAs low-dose chest CT protocol (effective dose of 1.80 ± 0.42 mSv) [17].…”
Section: Discussionmentioning
confidence: 76%
“…WHO issued recommendations on COVID-19 imaging, advocating the usage of a low-dose CT in adults with the disease [16]. Several studies confirm the applicability of low-and ultra-low-dose chest CT protocols for detecting typical COVID-19 pneumonia signs [17,18]. In practice, the effective dose given to COVID-19 patients may vary widely depending on the medical center, and it is generally higher than for patients with other pulmonary infectious diseases [19].…”
Section: Introductionmentioning
confidence: 99%
“…Quite often, protocols vary with regard to the associated radiation exposure and the desired image quality (IQ). There are already few reviews and evaluations published that compare different protocols with regard to the sensitivity and specificity of the diagnosis of COVID-19 [ 9 , 10 , 11 , 12 , 13 ]. Discrepancies in CT protocols for a particular organ or diagnostic inquiry are frequently observed within a single hospital, which is contingent upon the quantity of CT scanners and the diversity of vendors involved.…”
Section: Introductionmentioning
confidence: 99%